2009
DOI: 10.1182/blood-2007-05-089193
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional homologous recombination mediates genomic instability and progression in myeloma

Abstract: A prominent feature of most if not all cancers is a striking genetic instability, leading to ongoing accrual of mutational changes, some of which underlie tumor progression, including acquisition of invasiveness, drug resistance, and metastasis. Thus, the molecular basis for the generation of this genetic diversity in cancer cells has important implications in understanding cancer progression. Here we report that homologous recombination (HR) activity is elevated in multiple myeloma (MM) cells and leads to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
177
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(191 citation statements)
references
References 51 publications
14
177
0
Order By: Relevance
“…45 Increased homologous recombination activity and elevated expression of HR-related genes, including RAD51, has been suggested to mediate DNA instability and progression of MM. 46 FABP5 is expressed in various malignancies; it is a major target of the proto-oncogene c-MYC 47 and is involved in resistance of solid tumor cells to retinoic acid treatment.…”
mentioning
confidence: 99%
“…45 Increased homologous recombination activity and elevated expression of HR-related genes, including RAD51, has been suggested to mediate DNA instability and progression of MM. 46 FABP5 is expressed in various malignancies; it is a major target of the proto-oncogene c-MYC 47 and is involved in resistance of solid tumor cells to retinoic acid treatment.…”
mentioning
confidence: 99%
“…We have also found that if you treat cancer cells with nickel that further increases their HR and increases their ability to develop resistance to cancer treatment [2].…”
Section: Homologous Recombinationmentioning
confidence: 93%
“…More importantly, changes in DNA can also enable a cancer cell to become more aggressive and to resist cancer treatment. Data from our laboratory show that a major DNA repair system known as "homologous recombination" (HR) is overactive in some cancers [2]. Over activation of HR makes it defective and less precise, so instead of just fixing the damaged DNA it also gets involved in making unnecessary rearrangements…”
Section: Why Do Art Materials Have the Potential To Cause Health Probmentioning
confidence: 99%
“…Telomerases are reactivated in most cancers and immortalized cells. However, a subset of cancer/ immortalized cells lack telomerase activity and maintain telomere length by alternative mechanisms, probably involving genetic (homologous) recombination [Dunham et al, 2000], which is elevated in most immortal/cancer cell lines [Shammas et al, 2009].…”
Section: Structure and Function Of Telomeresmentioning
confidence: 99%